Peranan Kedutaan Besar Republik Indonesia dalam Menanggulangi Persoalan Tenaga Kerja Indonesia di Malaysia - Abdul Hariss (Universitas Batanghari Jambi, 2018)
The Government of the Republic of Indonesia that is obliged to protect its citizens wherever they are located, with negarannya commissioned the Embassy to address problems encountered. The one that needs to be done is legal protection for the workforce of Indonesia in particular who are in Malaysia, the role of the Embassy of Indonesia in Malaysia of which commissioned the Consular Affairs to handle Immigration Attaches correspondence ( Indonesia's labor Administration) in Malaysia as both travelers (tourists) as well as Indonesia's labor. When livelihoods work in the country's increasingly narrow then becomes one of a promising option in menompang a living life out to seek livelihoods abroad, one of which was Malaysia which became one of the main goals for the community Indonesia in search of a decent livelihood. Livelihood that promises to work outside the country raises many of the benefits of kindness as well as problems that arise either channelling legally or illegally, for the workforce in addition in the menafkahi family for labor Indonesia working outside the country will add to his family's prosperity for the regions in addition can also add defisa to the country so that workers who work outside of the country became the hero of the defisa for the State, then the labor should be given good legal protection. Because the State must be present to protect all the citizens of the respective countries anywhere.